Lietuvių tradicinis ir tautinis kostiumas : metodinė priemonė etnologijos specialybės studentams dėstomam kursui Lithuanian traditional and national costume - Venskienė, Asta (Vytautas Magnus University, 2010)
The teaching aid, which is designed for the students, provides condensed knowledge about traditional Lithuanian peasant women and men's clothes from ancient times to the beginning of the 20th century as well as a short overview of resources, iconographic materials, research and terminology. The origin of national clothes, folk costumes and the development of its concept in Lithuania and Eastern Europe is being analyzed. Lithuanian traditional costume is discussed in order to reveal its regional originality, to show the diversity of clothes in the territory of the same ethnographic region and to trace the impact of confession, of other nations and social status on peasant's costume.